The Impact of Investment on Local Community Development in Indonesia - Pertiwi, Claudya (Ipso Jure, 2024)
Investment is an activity that conducted by investing some capital then the invested capital is expected to provide an advantage for investors later. Investment is a thing which has a significant role for local communities because in its implementation the investment can give a considerable impact for the local community. However, the investment activities not only have a positive impact, but can also have a negative impact for sure. To reduce the negative effects that could be given by investment activities, we need to have an arrangement that we could give for the companies to develop local communities. The community development is an effort that we could made to improve the quality of a community who lives in an investment area which invested by investors, so that local people can chase the various fields of life that left behind. The writer use normative legal research methods which use library materials as source of data in writing this journal.